Pseudomonas Aeruginosa: Resistance to the Max - Poole, Keith (Frontiers in Microbiology, 2011)
Pseudomonas aeruginosa is intrinsically resistant to a variety of antimicrobials and can develop resistance during antipseudomonal chemotherapy both of which compromise treatment of infections caused by this organism. Resistance to multiple classes of antimicrobials (multidrug resistance) in particular is increasingly common in P. aeruginosa, with a number of reports of pan-resistant isolates treatable with a single agent, colistin. Acquired resistance in this organism is multifactorial and attributable to chromosomal mutations and the acquisition of resistance genes via horizontal gene transfer. Mutational changes impacting resistance include upregulation of multidrug efflux systems to promote antimicrobial expulsion, derepression of ampC, AmpC alterations that expand the enzyme’s substrate specificity (i.e., extended spectrum AmpC; ESAC), alterations to outer membrane permeability to limit antimicrobial entry and alterations to antimicrobial targets. Acquired mechanisms contributing to resistance in P. aeruginosa include β-lactamases, notably the extended-spectrum β-lactamases (ESBLs) and the carbapenemases that hydrolyze most β-lactams, aminoglycoside-modifying enzymes, and 16S rRNA methylases that provide high-level pan-aminoglycoside resistance. The organism’s propensity to grow in vivo as antimicrobial-tolerant biofilms and the occurrence of hypermutator strains that yield antimicrobial resistant mutants at higher frequency also compromise antipseudomonal chemotherapy. With limited therapeutic options and increasing resistance will the untreatable P. aeruginosa infection soon be upon us?